Analisis Kompetensi Kepemimpinan dan Budaya Organisasi Terhadap Kepuasan Pelanggan Melalui Perilaku Responsif (Studi pada PT Garuda Indonesia Kantor Cabang Surabaya) - Karimah, Yunia Insanatul (Jurnal Bisnis dan Keuangan, 2016)
The purpose of this research is to find out the influence of leadership competencyand organization culture to customer satisfaction either directly or indirectly throughresponsive behavior employees. This research has three variables namely independentvariables (leadership competency and organizational culture), mediating variable (responsivebehavior) and dependent variable (customer satisfaction). The population in thisresearch are frontliners and customer of PT Garuda Indonesia Surabaya Branch Office.The technique of data collection is the census method. Data are gathered by questionnairesgiven to 42 frontliners and customers of PT Garuda Indonesia Surabaya BranchOffice. This research used quantitative approach with multiple regression analysis. Theresult shows that leadership competency, organizational culture and frontliner responsivebehavior have significantly influence to customer satisfaction. Responsive behavior doesnot mediate the influence of leadership competency and organizational culture to customersatisfaction.